CONSTRAINTS FACED BY SHGS AND JLGS IN DAIRYING IN BARPETA AND KAMRUP DISTRICTS OF ASSAM - J. K. SAIKIA3, NABANEETA PATHAK1 ; K. K. SAHARIA2 (Indian Journal of Animal Production and Management, 2017)
A study was conducted to identify the constraints faced by the members of SHGs andJLGs in dairying in Barpeta and Kamrup districts of Assam. A total of 100 respondentsselected and information on their dairy characteristics and problems faced by them in dairyfarming were elicited through a structured, reliable and valid interview schedule. The resultshows about that high cost of feeds and fodder (83%), lack of quality breed (60%);inadequate veterinary facilities (56%), marketing (47%) etc were the major challenges ofdairying to mitigate.Keywords: Dairy, Constraints, Joint Liability Groups (JLGs), Self Help Groups (SHGs)